The urinary excretion of assayable vitamin B(12) and radioactivity after parenteral (58)Co B(12) in man - Adams, J. F. (1961)
Evidence is presented that after injection of radioactive vitamin B(12) in man, there is a close correlation between the amount of radioactivity excreted and the amount of assayable vitamin B(12) excreted, and thus that the amount of radioactivity excreted is a true measure of the vitamin B(12) excreted. The possible reasons for this occurrence are discussed and it is suggested that in the body vitamin B(12) does not exist as such but as an analogue or active derivative.